Pengaruh Model Pembelajaran Flipped Classroom terhadap Hasil Belajar Siswa Kelas V Pada Subtema 2 Hubungan Antar Makhluk Hidup dalam Ekosistem SD Negeri 091585 AFD VII Dolok Sinumbah - Yuliana Simanjuntak; Nancy Angelia Purba; Partohap Saut Raja Sihombing (Journal on Education, 2023)
This study aims to determine the effect of the Flipped Classroom Learning Model on the Learning Outcomes of Class V Students in Subtheme 2 Relationships Between Living Things in the Ecosystem of SD Negeri 091585 Afd VII Dolok Sinumbah. The research design was pre-experimental with a one-group pretest-posttest design. The population of this study were all fifth grade students at SD Negeri 091585 AFD VII Dolok Sinumbah, totaling 24 people. Because the population is less than 50, the population is used as a sample in this study. There are two hypotheses in this study, (1) there is an effect of the Flipped Classroom learning model on the Learning Outcomes of Class V Students in Subtheme 2 Relations Between Living Things in the Ecosystem of SD Negeri 091585 Afd VII Dolok Sinumbah (Ha), (2) there is no effect of the learning model Fliiped Classroom Against Learning Outcomes of Class V Students in Sub-theme 2 Relations Between Living Things in the Ecosystem of SD Negeri 091585 Afd VII Dolok Sinumbah (Ho). Data collection was carried out by giving multiple choice tests of 20 questions. Based on the results of inferential statistical analysis using the t-test it is known that the value of tcount is 5.444. At a significant level ɑ = 0.05, a ttable of 1,729 is obtained. then obtained tcount > ttable or 5.444 > 1.729. So it can be concluded that there is an influence of the Flipped Classroom learning model on the Learning Outcomes of Class V Students in Sub-theme 2 Relations Between Living Things in the Ecosystem of SD Negeri 091585 Afd VII Dolok Sinumbah. This means that Ha is accepted and Ho is rejected.